PENGARUH Pengaruh Growth Opportunity, Profitabilitas dan Free Cash Flow Terhadap Kebijakan Utang pada Perusahaan Farmasi Dibei - Violita Indah Permani; Ilzar Daud; Anggraini Syahputri; Anwar Azazi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Growth Opportunity, Profitability, and Free Cash Flow Related to Debt Policy are the main objectives of this study. Pharmaceutical companies traded on the Indonesia Stock Exchange (IDX) between 2019 and 2023 are the population of this study. Quantitative data used in this study comes from the Indonesia Stock Exchange (IDX) website (https://idx.co.id). The sample for this study was 14 companies over 5 years selected using purposive sampling techniques with several predetermined criteria. Based on the results of the study, Growth Opportunity does not affect debt policy, Profitability negatively affects debt policy, and Free Cash Flow does not affect debt policy.